PERAN LEMBAGA LOKAL DALAM PENATAAN RUANG DI KELURAHAN NGROTO, KECAMATAN CEPU, KABUPATEN BLORA - Hidayat, Andre Cahya; Manaf, Asnawi (Jurnal Pengembangan Kota, 2014)
A development that implements the concept of participation, involves the people in planning process, implementation, and also control the development program. In relation with implementation of participatory on development process, the Indonesian Government actualized it on PLP-BK program. PLP-BK is a spatial management program that implemented in rural or village. This program develops social capital in community level, particularly the established local institutions. Local institutions have an important role in the planning, implementation, control of this program, and also as a community representatives. The importance of local institutions on PLP-BK becomes the background of this research.The goal of research is to examine the role of local institutions in the implementation of PLP-BK at Ngroto Village, Cepu Sub-Regency, Blora Regency, Central Java. The goal is achieved by use a qualitative approach that called case study research. The analysis method are using qualitative description and domain analysis. The result of this research can explain the institutionalization process of spatial management in Ngroto. This process is mixing new values from the outside (i.e.spatial management) with local values in Ngroto through the roles of local institutions. The sustainability roles of local institutions is needed to achieve the result of this process, is called âpranata penataan ruangâ. Therefore, theÂ  researcher give a strategy and some actions to achieve the sustainability roles of local institutions in Ngroto, are: capacity building of local empowerment agent, partnership development, and preserve some local institutions. These actions to keep ongoing the institutionalization process in community level, although PLP-BK has ended at October 2012. Thus, community self-reliance can be achieved to realize the goal of spatial management in Ngroto